Are Changes in Food Consumption in the European Union Environmentally Friendly? - Dudek, Hanna; Koszela, Grzegorz; Krawiec, Monika (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2015)
Food production and consumption have significant impacts on the environment. Changes in consumption patterns typically entail changes in related production systems. Consumers through their consumption behavior, market demand for food, and choices between animal and vegetal products indirectly influence the environment. The paper is aimed at assessing changes in food consumption in the European Union with regard to their environmental impact. The empirical analysis covering the period from 2004 to 2011 is based on the most recent FAO data on calorie supply per capita and its split between animal and vegetal products. The investigation uses econometric models for panel data. Results obtained reveal a significant increase in supply from animal products in “new” EU members and a significant decrease in “old” EU members. In both groups, there is no significant change in supply from vegetal products, although they are not homogenous with regard to the food supply.